PEMANFAATAN POWERPOINT TERINTEGRASI DENGAN I-SPRINGPRESENTER SEBAGAI MEDIA PEMBELAJARAN ICT - Khusnul Khotimah (Eksponen, 2019)
The use of technology in the field of education has become a fundamental necessity. One such technological involvement can be seen in the learning activities in the classroom. Many applications/software that can be used as a learning tool, two of which are Microsoft Powerpoint and ispring presenter. Microsoft Powerpoint Application integrated ispring presenter can be used as an alternative in the creation of ICT learning media. Learning Media is produced by obsermving the right design supported by various animations, audio/video making the learning process more interesting, the presentation of the material becomes more effective so that it will be easier To be understood by learners.